1943
DOI: 10.1017/s0021859600007140
|View full text |Cite
|
Sign up to set email alerts
|

The relation between rates of growth and rickets in sheep on diets deficient in vitamin D.

Abstract: The blood picture for Ca, inorganic P and phosphatase during the development of rickets caused by uncomplicated vitamin D deficiency in sheep has been established. The earliest and most distinctive change was found to be in the serum Ca level.Lambs were shown to have sufficient reserves of vitamin D to protect them against avitaminosis D for a period of about 6 weeks as judged by serum Ca levels. Rickets did not develop unless there was a moderate degree of growth and, in such cases, the serum Ca level was bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1951
1951
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…It was observed that certain sheep in every group consistently gave phosphatase values considerably above or below the mean for the group, so that differences between individuals within some groups were larger than the mean group differences. This confirms the observations made by Duckworth et al (1943) that plasma-phosphatase values in sheep are not of much diagnostic value.…”
Section: Blood Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that certain sheep in every group consistently gave phosphatase values considerably above or below the mean for the group, so that differences between individuals within some groups were larger than the mean group differences. This confirms the observations made by Duckworth et al (1943) that plasma-phosphatase values in sheep are not of much diagnostic value.…”
Section: Blood Compositionsupporting
confidence: 91%
“…Franklin (1934-5) has shown that a diet low in Ca could cause pathological changes in the bones of sheep which Innes (1934-5) suggested might be regarded as 'rickets'. Moreover, Duckworth, Godden & Thomson (1943), in their study of the development of rickets in sheep where a diet containing 1-6 g. Ca and 1.9 g. P was given, maintained that the most constant diagnostic sign of the onset of the disease was a fall in the serum Ca below 6 mg./ I 0 0 ml.…”
Section: Dietmentioning
confidence: 99%
“…It was Duckworth, Godden and Thomson (1943) who showed that rickets in sheep could be produced by keeping them inside and feeding a vitamin D-free ration. The sheep fed a high calorie diet and with the fastest rate of weight-gain were those with the highest incidence of rickets.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier New Zealand field trials in which cod-liver oil was given in a dosage of approximately 300 international units daily to wethers and rams grazing green oats, a number of wethers became mildly rachitic and two of the four rams showed fairly severe rickets upon this level of intake. I n the experiment already referred to, in which Scottish blackface sheep were used (Duckworth et al, 1943), the dosage of vitamin D was at the rate of 200-250 international units daily per 100 lb. body weight and this was sufficient to prevent development of leg weakness, to ensure good growth and normal blood composition.…”
Section: Introductionmentioning
confidence: 99%